Impacts of Low Self-Control and Delinquent Peer Associations on Bullying Growth Trajectories Among Korean Youth: A Latent Growth Mixture Modeling Approach - Cho, Sujung (Journal of interpersonal violence, 2021)
The emergence of studies applying Gottfredson and Hirschi’s (1990) self-control theory to offending behaviors has produced empirical support confirming the position that individuals with low self-control are more likely to engage in deviant behaviors. However, few have examined its effects with opportunity factors. The present study examines the time-invariant effect of low self-control, as well as the time-concurrent and lagged effects of opportunity factors (parental attachment and delinquent peer associations), on bullying growth trajectories. The findings in the latent growth curve analysis demonstrate that low self-control is significantly related to both the initial levels and change in bullying over time, even after controlling for delinquent peer associations in homogeneous populations. The new approach described within the latent class growth modeling framework (i.e., growth mixture) incorporates a categorical latent trajectory variable representing latent classes (i.e., distinct subgroups), having similar patterns of bullying growth trajectories. Three groups of students emerged from the student-reported data at five time points from ages 11 to 15, decreasers (90%), moderate late peakers (7%), and high late peakers(3%), defined by different predictors and sequelae. Low self-control was rendered insignificant for both moderate late peakers and high late peakers relative to decreasers; delinquent peer associations had a time-concurrent effect for moderate late peakers than decreasers; and high late peakers had a time-lagged effect relative to moderate late peakers.